Contemporary education dialogue
Contemporary Education Dialogue serves as an independent open forum for researchers and practitioners to sustain a critical engagement with issues in education by engendering a reflective space that nurtures the discipline and promotes inter-disciplinary perspectives. The journal allows for a refinement of theoretical and practical basis for improving the quality of education, furthering the opportunity to directly create reflective classroom practices.